Effect Of Heparin On The Thrombin-Antithrombin Reaction Product - Danishefsky, Isidore; Bender, Michael S (Thrombosis and Haemostasis, 1981)
The characteristics of the primary complex (C-l) formed between thrombin and antithrombin in the absence and presence of heparin, were investigated. Each of the complexes were isolated by gel-filtration of the reaction mixture on Sephadex G-100.Analyses by SDS-polyacrylamide gel electrophoresis showed that thrombin causes the successive degradation of both complexes to lower molecular weight products C-2 and C-3, respectively. C-l that was formed in the absence of heparin also undergoes spontaneous direct degradation at pH 7.5, to a complex that is similar to C-3. Additionally, this C-l dissociates very slowly to release thrombin, as demonstrated by its action on a synthetic substrate. Treatment of C-l with 1M NH2OH results in its breakdown to thrombin and antithrombin. The complex formed in the presence of heparin differs from the one formed without heparin, in that it does not exhibit any measurable dissociation and does not undergo breakdown to the C-3-type product. Moreover, whereas C-l formed in the absence of heparin is decomposed completely by 1M NH2OH, the complex formed in the presence of heparin undergoes only partial breakdown even with 2M NH2OH. Addition of heparin to C-l originally produced in the absence of heparin, has no effect on its properties.The results thus indicate that heparin influences the mode of binding between thrombin and antithrombin as well as the rate of their interaction.